2
$\begingroup$

I'm reading this lecture notes (Lecture III: Ashtekar variables for general relativity) about Tetrad Formalism in General Relativity. In page 8-9 the Palatini action is defined (basically the Einstein-Hilbert action but in function of tetrads $e$ and the Lorentz action $\omega$);

\begin{equation} {\displaystyle S=\frac{1}{16\pi G}\int_M d^{4}x\;|e|\;e_{I}^{\mu }e_{J}^{\nu }{F _{\mu \nu }}^{IJ}(\omega)} \end{equation}

Thus, the autor say that $\varepsilon^{\mu \nu c d} \epsilon_{IJKL}e^K_c e^L_d=2ee_I^{[\mu}e_J^{\nu]}$ allows us to rewrite the Palatini action above in differential-form notation as follows: \begin{equation} {\displaystyle S=\frac{1}{64\pi G} \int_M \epsilon_{IJKL} e^K\land e^L \land {F }^{IJ}(\omega)} \end{equation}

But, even with this hint I don't see how to obtain this last expression using the first. Thanks in advance for any hint.

$\endgroup$
0
3
$\begingroup$

I am going to assume that $F_{[ab]}=\tfrac12\left(F_{[ab]}-F_{[ba]}\right)$. Hence,

$e^a_Ie^b_JF^{IJ}_{ab}=e^{[a}_Ie^{b]}_JF^{IJ}_{ab}$

Since the field strength is antisymmetric. Also,

$d^4x|e|e^{[a}_Ie^{b]}_JF^{IJ}_{ab}=d^4x|e|\frac{1}{2e}\epsilon^{abcd}\epsilon_{IJKL}e^K_ce^L_dF^{IJ}_{ab}=\tfrac12\text{sgn}(e)d^4x\epsilon^{abcd}\epsilon_{IJKL}e^K_ce^L_dF^{IJ}_{ab}=\tfrac14\epsilon_{IJKL}\mathbf{e}^K\wedge\mathbf{e}^L\wedge\mathbf{F}^{IJ}$ where I've used the definition of the wedge product and the one form. The result follows immediately.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.